Youth Gangs, Racism, and Schooling Vietnamese American Youth in a Postcolonial Context - Lam, Kevin D.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2015)
Winner of the American Educational Studies Association 2016 Critics' Choice Book Award Youth Gangs, Racism, and Schooling examines the formation of Vietnamese American youth gangs in Southern California. Lam addresses the particularities of racism, violence, and schooling in an era of anti-youth legislation and frames gang members as post-colonial subjects, offering an alternative analysis toward humanization and decolonization.
Keywords: Ethnology—Asia.; Sociology; Education; Education—History.; Juvenile delinquents; Philosophy and social sciences; Asian Culture; Sociology, general; Education, general; History of Education; Youth Offending and Juvenile Justice; Philosophy of Education